Reflections on Methodological Congruence in Systems and Complexity-Informed Research; Comment on "What Can Policy-Makers Get Out of Systems Thinking? Policy Partners' Experiences of a Systems-Focused Research Collaboration in Preventive Health" - Ana Teixeira de Melo (Kerman University of Medical Sciences, 2021)
In this paper we argue, for an increased congruence between the conceptual frameworks and the research methodology in studies focused on the theory or practice of systems and complexity-informed thinking (SCT). In doing so, we believe we can build more complex forms of knowledge with clearer and more impactful implications for practice. There is scope for both methodological innovations and the adaptation of traditional research methods to enact properties congruent with the systemic complexity of our targeted realities. We organise our reflection around the paper of Haynes et al. We provide examples of how a research methodology more deeply embedded in systems and complexity-thinking may add depth and meaning to the research results and their interpretation. We explore the creative adaptation of the interview techniques to integrate systemic forms of questioning (eg, circular and reflexive questioning) to map the patterns of interaction contributing to the outcomes of interventions.